The experimental study of solder creep - Leo, Jasper Yao An (Nanyang Technological University, 2020)
In these modern days, climatic change and environmental pollution is a pressing crisis. Many countries and companies are putting in efforts into the research of more environmentally friendly products as well as campaigns and initiatives. Amongst all these environmental pollutions, electronic waste (e-waste) is one of the largest and fastest growing in the municipal solid waste stream. In 2020, its estimated more than 50 million tons of e-waste will be created in the world and is expected to grow 8% per year [1]. Electronic wastes comprise of various layers and micro connection is one of the most important components in them. Soldering is one of the most common method of joining components together. Usually, solders are metal alloys containing lead and when it is cooled, a strong electrical bond is created [2,3]. However, with lead being a very hazardous element to the environment and humans as well [4], many semiconductor packages and electronics that are manufactured uses these lead-free solders for integrated circuit (IC) assembly, on the surface for mounting, silicon chip interconnections and different elements on a printed circuit board (PCB). So as to ensure the efficiency and effectiveness of such lead-free solder materials in the ICs and PCBs, one will have to understand the mechanical properties, physical properties and the solder joint reliability performance in service. This report will thus evaluate these solders namely the 99.3Sn–0.7Cu (tin–copper) lead-free solder alloy’s mechanical properties with comprehensive test results from creep tests carried out under different temperatures and loads using the Shimadzu (10kN) tensile testing machine.